Physical and Chemistry Characteristics of Ice Cream with Additional Bitter Melon Puree - Kukuh Saputryasto; Titi Mutiara Kiranawati; Laili Hidayati (Bulletin of Culinary Art and Hospitality, 2021)
Ice cream made from added with bitter melon puree it is hoped will get a unique taste. The processing of this ice cream utilizes the abundant yield of bitter melon from an area. This study aims to examine the chemical properties (vitamin C, and β-carotene) and physical properties (viscosity, overrun, and melting power). The type of research used is experimental research. The design in this study used a completely randomized design (CRD) with one treatment, namely the addition of bitter melon puree with three percentages (50 percent, 40 percent, 30 percent). The data obtained were then analyzed using the ANOVA method if there was a difference followed by DMRT. There are significant differences in vitamin C levels, β-carotene levels, viscosity, overrun value, and melting power. The highest levels of vitamin C were found in the addition of bitter melon puree by 50 percent, the highest β-carotene levels were found in the addition of bitter melon puree by 50 percent, viscosity was found in the addition of bitter melon puree by 50 percent, the highest overrun value was found in the addition of bitter melon puree by 50 percent, and the highest melting power was found in the addition of bitter melon puree by 50 percent. The conclusion obtained from this study is that the addition of more bitter melon puree will increase levels of vitamin C, β-carotene levels, viscosity, overrun, and melting power.